Examining the determinants of millennials' repurchase intention for electronic products on Tokopedia using UTAUT2 - Alhamnovanda, Syakura; Asikin, Zenal; Jahroh, Siti (International Journal Labs, 2024)
In Indonesia, internet usage has created substantial growth potential for e-commerce, particularly among millennials, who dominate as the primary users of e-commerce platforms. However, consumer behavior in purchasing electronic products online remains complex and challenging. This study aimed to examines the factors influencing millennials' intention to repurchase electronic products on Tokopedia. Involving 398 respondents’ millennial consumers. Data were collected through an online questionnaire. The Unified Theory of Acceptance and Use of Technology (UTAUT2) was applied to examines the effects of performance expectancy, effort expectancy, hedonic motivation, habit, facilitating conditions, price value, social influence, and with additional variable trust on variable independent, intervening (satisfaction), and dependent (repurchase intention) variables. Data analysis was conducted using PLS-SEM. The findings show that performance expectancy, effort expectancy, hedonic motivation, habit, facilitating conditions, and social influence positively and significantly influence customer satisfaction, while price value and trust do not show significant influence. Customer satisfaction also mediates the relationship between several of these variables and repurchase intention. This study provides practical implications for e-commerce platform managers, such as enhancing platform performance, developing features that trigger positive emotional experiences, utilizing customer behavior data, and strengthening technical support and social elements in marketing strategies.